Islamic Educational Thought and Challenges of The Revolution Industry 4.0 and Society 5.0 - Dahlia; Almawadi; Maltifal; Riki Saputra; Syafril Syafril (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The rapid development of the Industrial Revolution 4.0, driven by digitalisation, artificial intelligence, and Big Data, together with the emergence of human-centred Society 5.0, requires a fundamental transformation of Islamic education. This study aims to analyse the epistemological, axiological, pedagogical, socio-cultural, and economic challenges faced by Islamic educational institutions in responding to digital technology disruption, and to formulate integrative-contextual solutions. This research used a descriptive qualitative approach through library research. Data were analysed critically and philosophically using content analysis of classical and contemporary Islamic educational thought. The findings show four latent problems that hinder the acceleration of Islamic education, namely cultural lag, second-class stigma, the dichotomy of sciences, and dualism in educational policy. The study proposes knowledge integration through an integrative-interconnected paradigm, adab-based character strengthening, digital tarbiyah, innovative learning methods, and adaptive curriculum reconstruction. Tawazun, Ulul Albab, and Iqra’ serve as theological foundations for developing intellectually excellent, technologically adaptive, spiritually strong, and morally noble Muslim generations.